2022
DOI: 10.1111/2041-210x.13973
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a coastal acoustic buoy for cetacean detections, bearing accuracy and exclusion zone monitoring

Abstract: 1. There is strong socio-political support for offshore wind development in US territorial waters and construction is planned off several east coast states. Some of the planned development sites coincide with important habitat for critically endangered North Atlantic right whales. Both exclusion zones and passive acoustic monitoring are important tools for managing interactions between marine mammals and human activities. Understanding where animals are with respect to exclusion zones is important to avoid cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The above studies [39][40][41][42][43][44][46][47][48], including our present study, highlight promising perspectives for cetacean population monitoring and reasonable price/energy cost acoustic transects [6,49]. However, precautions must be taken when trying to estimate population densities with a surface autonomous vehicle [38,50,51] as the usual assumption, that the animal's speed is slow compared with the vessel's speed, is violated.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…The above studies [39][40][41][42][43][44][46][47][48], including our present study, highlight promising perspectives for cetacean population monitoring and reasonable price/energy cost acoustic transects [6,49]. However, precautions must be taken when trying to estimate population densities with a surface autonomous vehicle [38,50,51] as the usual assumption, that the animal's speed is slow compared with the vessel's speed, is violated.…”
Section: Resultsmentioning
confidence: 78%
“…PAMGuard has been used extensively and successfully in the detection of marine mammals in the mitigation and renewable energies contexts, such as beaked whales (through automatic detection of their clicks) [40], seals and porpoises [41], and whales [42,43]. Studies on the performance of PAMGuard have shown that for whistles, the recall can reach up to 79.6% [39].…”
Section: Resultsmentioning
confidence: 99%